Managing Pregnancy with Post Mitral Valve Replacement Presenting Late - Lamichhane, Basanta; Paradhan, N; Rawal, SJ; Singh, A; Bhandari, SR; Manandhar, R (Nepal Journal of Obstetrics and Gynaecology, 2013)
With the increased awareness and emphasis of institutional delivery, there has been an increase in trend of cases of valvular heart disease with pregnancy being reported to tertiary centers. Though rare, cases like post mitral valve replacement (MVR) with pregnancy are often a challenge in terms of management with an outcome of uneventful pregnancy and healthy baby. The management of women with prosthetic heart valves during pregnancy poses a particular challenge as there are no available controlled clinical trials to provide guidelines for effective antithrombotic therapy. Here we present a case of post MVR with pregnancy with an ultimate outcome of a healthy female and uneventful vaginal delivery. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 50-52 DOI: http://dx.doi.org/10.3126/njog.v8i1.8866